Survey of Students' Gadget Utilization to Know the Readiness of Personal Digital Inquiry Learning Implementation - Mahmudah Nur Cahyaningrum; Topik Hidayat; Kusnadi (Postgraduate, University of Mataram, 2024)
This study aims to determine the readiness of students and resources to implement Personal Digital Inquiry (PDI) learning. The research method was conducted by survey. The survey was conducted on public high school students in Depok city. 346 respondents were willing to answer 19 questions through a Google Form. Questions were asked in the form of multiple choice, checkbox, and short answer, including class, age group, as well as questions about gadgets and their utilization. The survey results were presented in graphical form and analyzed descriptively. The results of the analysis show that overall students and teachers are ready to implement PDI learning. Students have gadgets that qualify as one of the means in the implementation of PDI; students have also been accustomed to utilizing gadgets for learning even though they have not been maximized; students' proximity to social media can be used as an opportunity to be integrated in PDI learning; students are familiar and accustomed to utilizing various applications and search sites that can support the process of implementing PDI. Some obstacles to the use of gadgets can be taken into consideration in the preparation of PDD implementation scenarios.